Monitoring inrush risk with mXrap: from idea to reality - Teet, R; Mowen, J (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Inrush events pose a significant hazard in block and sublevel cave operations, with historical incidents resulting in fatalities and ongoing operational risks. Effective management of this hazard requires timely interpretation and communication of complex datasets, yet traditional approaches often rely on fragmented tools and manual processes that limit visibility and responsiveness. This paper presents the development of a customised inrush management application within the mXrap (Harris & Wesseloo 2015) platform, designed to integrate multiple data sources and provide an intuitive, visual interface for risk assessment. Over a 24-month period, Resolve Mining Solutions collaborated with several established block cave operations to transform a conceptual idea into a functional and commercially available tool that supports both operational and management decision-making. Key features include the import and visualisation of drawpoint observations, rainfall tracking, and integration of GEOVIA PCBC (2026) data for fines prediction. The application calculates inherent and residual risk using site-specific trigger action response plans, displays results in 3D, and enables time-based filtering for trend analysis. Additional enhancements include heatmaps, observation-versus-prediction comparisons, and spill event visualisation to improve communication of risk across the workforce. By leveraging existing mXrap functionality and applying targeted customisations, this project demonstrates that advanced hazard management tools can be developed without extensive programming expertise or high cost. The resulting platform reduces reliance on multiple applications, improves transparency, and provides a scalable framework for managing one of the most critical hazards in caving operations.
Keywords: inrush